2015
DOI: 10.1002/anie.201500970
|View full text |Cite
|
Sign up to set email alerts
|

Formation of BN Isosteres of Azo Dyes by Ring Expansion of Boroles with Azides

Abstract: Herein, we present the results of our investigations on the effect of ortho substitution of aryl azides on the ring-expansion reaction of boroles, five-membered unsaturated boron heterocycles. These studies led to the isolation of the first 1,2-azaborinine-substituted azo dyes, which are bright yellow solids. One of the derivatives, (E)-2-mesityl-1-(mesityldiazenyl)-3,4,5,6-tetraphenyl-1,2-azaborinine, was found to be unstable in solution and to transform through a Jacobsen-like reaction into an indazole and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
80
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 115 publications
(86 citation statements)
references
References 59 publications
2
80
0
3
Order By: Relevance
“…[3] The similarity of carbon and its BN derivatives is well documented in chemistry, including the graphite/hexagonal boron nitride, and benzene/1,2-dihydro-1,2-azaborine pairs, including their Dewar forms. [4] However, evidence for the existence of BN-arynes is scarce and indirect as it comes from a self-trapping experiment. [5] Here we show by direct spectroscopic techniques that 1,2-azaborine can exist as reactive intermediate.…”
mentioning
confidence: 99%
“…[3] The similarity of carbon and its BN derivatives is well documented in chemistry, including the graphite/hexagonal boron nitride, and benzene/1,2-dihydro-1,2-azaborine pairs, including their Dewar forms. [4] However, evidence for the existence of BN-arynes is scarce and indirect as it comes from a self-trapping experiment. [5] Here we show by direct spectroscopic techniques that 1,2-azaborine can exist as reactive intermediate.…”
mentioning
confidence: 99%
“…1, II). 37 During the reaction of 1,2,3,4,5-pentaphenylborole (1) with Me 3 SiN 3 , Martin et al trapped an eight-membered ring system in which all of the three nitrogen atoms of the azide are incorporated into the borole ring ( Fig. 1, III).…”
mentioning
confidence: 99%
“…Experimental and computational mechanistic investigations on the reaction of TMSN 3 and pentaphenylborole 1 revealed that the reaction is initiated by adduct formation via coordination of the α--nitrogen to the boron center (Int11). 52 The differing reactivity can be rationalized by the α--nitrogen acting as the nucleophilic site in the production of 18, whereas bulky groups prevent coordination via this nitrogen, and as a consequence, the γ--nitrogen coordinates to give Int13 that subsequently undergoes a 1,1--insertion reaction to yield the azobenzene analogues 21 and 22. 50 A higher energy pathway originating from Int12 was also observed, producing 1,2--azaborine 18 as the thermodynamic product and N 2 as a byproduct.…”
Section: Coordination Ring Expansion Reactivitymentioning
confidence: 99%